Haematological Changes In Open Cervix Pyometra Following Pgf2α Therapy In Canines - Mohan, P.; Subramanian, A.; Nambi , A.P. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Canine pyometra is a common reproductive disorder of intact diestrual bitch, which warrants early recognition, diagnosis and appropriate treatment to avoid any disastrous consequences. A total of 36 bitches of different breeds and age were divided into three groups consisting of twelve bitches in each group. Animals of Group I were treated with PGF2α @ 250 µg/kg body weight once daily for five days, and those of Group II were treated with PGF2α @ 30 µg/kg body weight twice daily for eight days subcutaneously. Both the above groups including Group III (non-PGF2α control) were treated with selected antibiotics (Cefataxime, Amikacin etc) parenterally for seven days based on antibiogram results at standard dosage. The effect of PGF2α treatment on haematological changes in open type of pyometra revealed no changes in total erythrocyte count, haemoglobin and packed cell volume, while there was marked neutrophilic leucocytosis, monocytosis and shift to left (immature neutrophils).
Keywords: Open cervix pyometra; PGF2α; bitches; haematology